2008
DOI: 10.1007/s00018-007-7488-x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondins: from structure to therapeutics

Abstract: Thrombospondin-1 is secreted protein that modulates vascular cell behavior via several cell surface receptors. In vitro, nanomolar concentrations of thrombospondin-1 are required to alter endothelial and vascular smooth muscle cell adhesion, proliferation, motility, and survival. Yet, much lower levels of thrombospondin-1 are clearly functional in vivo. This discrepancy was explained with the discovery that the potency of thrombospondin-1 increases more than 100-fold in the presence of physiological levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(67 citation statements)
references
References 133 publications
2
64
0
1
Order By: Relevance
“…Several receptors of TSP1 have been implicated in its antiangiogenic activity (11,31,46), but their functions may be distinct. CD36 is necessary for TSP1 to inhibit FGF2-stimulated angiogenesis in rat cornea (13), but it is not clear that this requirement extends to VEGF-stimulated angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several receptors of TSP1 have been implicated in its antiangiogenic activity (11,31,46), but their functions may be distinct. CD36 is necessary for TSP1 to inhibit FGF2-stimulated angiogenesis in rat cornea (13), but it is not clear that this requirement extends to VEGF-stimulated angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Ligation of CD47 Is Sufficient to Inhibit VEGFR2 Phosphorylation-TSP1 inhibits endothelial cell NO/cGMP signaling via CD47 at Ն10 pM concentrations (31). To explore the possibility that TSP1 also regulates VEGFR2 phosphorylation via CD47, we first used the TSP1-derived CD47-binding peptide 7N3 (FIRVVMYEGKK).…”
Section: Tsp1mentioning
confidence: 99%
“…Ser 64 of CD47 Is Essential for Inhibiting T Cell ActivationPrevious studies have shown that TSP1 inhibits T cell activation induced by antibody engagement of the T cell receptor component CD3 (26,27). Activation of WT Jurkat cells using CD3 antibody increased expression of mRNA for the early activation marker CD69 by 80-fold at 2 h (Fig.…”
Section: Cd47 Is Modified With Heparan and Chondroitin Sulfatementioning
confidence: 91%
“…Identification of GAG Modification Sites on CD47-Based on the previously defined amino acid sequence parameters for GAG modification (52) and a crystal structure for the recombinant extracellular domain of CD47 (53), we identified Ser 64 and Ser 79 as surface-exposed residues that could be potential acceptors for GAG addition (Fig. 7E).…”
Section: Cd47 Is Modified With Heparan and Chondroitin Sulfatementioning
confidence: 98%
See 1 more Smart Citation